DETERMINANTS OF FINANCIAL STATEMENT FRAUD: THE PERSPECTIVE OF PENTAGON FRAUD THEORY (PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Ashila Larasati , Latisha; Kusumaningsih, Ambar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to determine the effect of elements contained in the fraud pentagon, namely pressure, opportunity, rationalization, Competence, Arrogance on Financial Statement Fraud. Financial Statement Fraud is measured by F-Score. Pressure is proxied by financial target, financial stability, and external pressure. Opportunity is proxied by ineffective monitoring and Quality of external auditor. Rationalization is proxied by Change in Auditor. Competence is proxied by Change in Director. Arrogance is proxied by frequent number of CEO's Picture. The data used in this study are secondary data obtained from the annual reports of banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The number of samples used was 72 samples from 24 companies selected through purposive sampling techniques. The data analysis method used in this study is logistic regression analysis The results of the study show that financial stability, change in auditor, change in director, and number of CEOs do not affect financial statement fraud. On the other hand, things like Financial Target, External Pressure, Ineffective monitoring, and Quality of External influence financial statement fraud.